ANALISIS HUBUNGAN HAMBATAN OPERASIONAL DENGAN KINERJA PENDAPATAN USAHA E-COMMERCE DI INDONESIA - Herlina, Erna; Mujito; Anwar, Syaiful (ITB AAS Indonesia Surakarta, 2025)
E-commerce businesses in Indonesia have grown with high revenues. However, e-commerce is still a challenge due to changes in marketing and payment methods. Various barriers are faced by e-commerse business actors in Indonesia. This study aims to determine the relationship between e-commerse business barriers and e-commerse revenue. This research is a quantitative research. The research was conducted on e-commerse businesses from all provinces in Indonesia. This study uses secondary data from BPS (2021). Data were analysed with Pearson correlation test. The results show that lack of capital has a moderate and negative relationship with e-commerse revenue. Lack of demand for goods/services has a moderate and positive relationship with e-commerse revenue. Lack of skilled labour, limited internet access, fraud in the buying and selling process, and limited delivery services are not significantly related to e-commerse revenue